2014
DOI: 10.4238/2014.july.24.11
|View full text |Cite
|
Sign up to set email alerts
|

Flaxseed oil supplementation alters the expression of inflammatory-related genes in dogs

Abstract: ABSTRACT. Long chain n-3 fatty acids are beneficial to mammals because of their anti-inflammatory role. However, whether flaxseed oil, which is rich in short chain n-3 fatty acids, has such a role, it has not been extensively examined. This study investigated the supplementation of flaxseed oil on the regulation of genes involved in inflammatory responses such as heat shock proteins (HSP90 and HSP70) and interleukin (IL1β) in the white blood cells of dogs. Five beagles and 5 greyhounds were supplemented with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…However, the use of flaxseed as a source of omega-3 fatty acids, and in particular the fatty acid ALA, in cat diets is often dismissed due to their inability to convert ALA to EPA and DHA. More recent evidence in human, companion animal, and pre-clinical models suggests that ALA itself has immunomodulatory benefits [ 5 , 13 , 21 , 22 ]. Although it has been reported that cats have low delta-6 desaturase activity, there is evidence that at least in liver and brain tissue specifically, synthesis of long-chain omega-3 fatty acids can be achieved in the absence of dietary EPA, DPA, and DHA in cats [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the use of flaxseed as a source of omega-3 fatty acids, and in particular the fatty acid ALA, in cat diets is often dismissed due to their inability to convert ALA to EPA and DHA. More recent evidence in human, companion animal, and pre-clinical models suggests that ALA itself has immunomodulatory benefits [ 5 , 13 , 21 , 22 ]. Although it has been reported that cats have low delta-6 desaturase activity, there is evidence that at least in liver and brain tissue specifically, synthesis of long-chain omega-3 fatty acids can be achieved in the absence of dietary EPA, DPA, and DHA in cats [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that ALA and LA increased from d15 to d22, suggesting that enrichment of these fatty acids in circulation is not stabilized after 3 weeks of feeding [ 4 ]. Interestingly, a more recent study in both beagles and greyhounds investigated feeding 100 mg/kg food of flaxseed oil on plasma fatty acid levels and their link to inflammatory responses such as heat shock protein 90, heat shock protein 70, and interleukin 1-beta [ 5 ]. There, flaxseed oil supplementation increased ALA and EPA concentrations and downregulated the expression of heat shock protein 90 and interleukin 1-beta in greyhounds but not in beagles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors suggest that fatty acids might influence inflammation and oxidative stress, depending on the chain length and the degree of saturation, although there is little information regarding the optimal fat intake for canine athletes [ 1 ]. Certain results indicate the beneficial effect of eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and omega-3 long-chained polyunsaturated fatty acids (LC PUFA) on canine health [ 2 ]. Studies have shown that the supplementation of food-derived alpha-linolenic acid (ALA), the dietary precursor of EPA and DHA, might lead to the accumulation of EPA and docosapentaenoic acid (DPA), but rarely of DHA in dogs [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%